Reducing waiting time and raising outpatient satisfaction in Chinese public tertiary hospitals: an interrupted time-series study. (December 2017) - Sun, Jing; Li, Hong; Lin, Qian; Zhang, Qiongyao; Xu, Kai; Chen, Huiying; Zhao, Pengyu; Fu, Hongyu; Hu, Cecile J; Stuntz, Mark; Liu, Yunali
Abstract: Background: It is globally agreed that a well-designed health system delivers timely and convenient access to health services for all patients. Many interventions aiming to reduce waiting times have been implemented in Chinese public tertiary hospitals to improve patients' satisfaction. However, few interventions were well documented, and the effects were rarely measured with robust methods. Methods: We did a longitudinal study of the length of waiting times in a public tertiary hospital in southern China, which developed comprehensive data collection systems. Data were extracted from the hospital's information systems and patient satisfaction surveys. We analysed longitudinal time-series data using a segmented linear regression model with SPSS 21·0 to assess changes in levels and trends of waiting times before and after the introduction of waiting time reduction interventions. Pearson correlation analysis was done to indicate the strength of association between waiting times and patient satisfactions. The statistical significance level was set at 0·05. Findings: The monthly average length of waiting time decreased by 3·49 min (p=0·003) for consultations and by 8·70 min (p=0·02) for filling prescriptions in the corresponding month in which respective interventions were introduced. The trend shifted from baseline from a slight increase to a significant decrease in time for filling prescriptions (p=0·003). We found a significant negative correlation between waiting time of filling prescriptions and outpatient satisfaction towards pharmacy services (r=–0·71; p=0·004). Interpretation: The interventions aimed at reducing waiting time and raising patient satisfaction in Fujian Provincial Hospital are effective. A long-lasting reduction on waiting time for filling prescriptions was observed because of carefully designed continuous efforts, rather than a one-time campaign, and with appropriate incentives implemented by a taskforce authorised by the hospital managers. This case provides a model of continuous quality improvement and optimisation of management process with the support of relevant evidence. Funding: National Health and Family Planning Commission of China.